IN A NEW STAGE OF DEVELOPMENT OBJECTIVE NEED TO REFORM PUBLIC SERVICES - Abdumalikov Abdulatif Abidjanovich; Kadyrov is the son of Shokhrukhbek Musajon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Based on the general purpose of this research, important theoretical and practical issues of public service, state-service relations, problems in this area and ways to solve them, ways to form and improve knowledge about foreign experience and practice, professional ethics of a public servant, influence on it the study of the indicators was analyzed according to the purpose.